The Influene of Financial Literacy, Financial Attitudes and Self Efficacy on the Use of Paylater in Generation Z - Isrofiati, Rosida; Isnaini, Zuhrotul (PT FORMOSA CENDEKIA GLOBAL, 2024)
Many online shopping applications are now equipped with a buy now pay later method or better known as paylater. The widespread use of paylater to interact in all types of online transactions helps make buying and selling activities easier. The existence of a buy now pay later system makes people interested in using paylater. The purpose of this study is to determine the effect of financial literacy, financial attitudes and self-efficacy on the use of paylater in generation z. The research method uses quantitative. Data analysis was performed with PLS (Partial Least Square) using Smart PLS 3.0. The results showed that the three independent variables had a significant effect on the dependent variable.